ANALISIS KINERJA PENGELOLAAN KEUANGAN DAERAH PEMERINTAH KOTA BALIKPAPAN - Umam, Muhammad Khaerul; Rochinda, Eny; Suharto, Rahcmad Budi (Universitas Nusa Cendana, 2024)
This research aims to analyze the financial management performance of the Balikpapan City Regional Government using income variance analysis, degree of decentralization ratio, independence ratio, income growth ratio, efficiency analysis, effectiveness analysis, capital expenditure ratio, and operational expenditure ratio in the Balikpapan City Government for the budget year 2016 to 2022. The data used is secondary data contained in the Audit Results Report of the Republic of Indonesia Financial Audit Agency Representative of East Kalimantan Province for 2016 to 2022. Static analysis in this study uses descriptive quantitative methods. The observation period from 2016 to 2022 shows that income variance analysis is the best average achievement of 101.20%; the degree of decentralization ratio with an average achievement of 29.48%; independence ratio to average achievement is 42.87%; local original income ratio with an average achievement of 5.87%; total regional income ratio to average achievement is 4.50%; the efficiency level ratio with an average achievement of 96.80% is declared less efficient; the effectiveness level ratio with an average achievement of 108.43% was declared less effective, the capital expenditure ratio with an average achievement was 72.58%; operational expenditure ratio with average achievement of 25.98% Keywords: Local Finance; Financial Performance; Financial Ratio